On convergence of the sums of the Markov renewal processes to a Poisson process - Sapagovas, J. (Lithuanian Mathematical Journal, 1966)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: И. Сапаговас. О сходимости сумм марковских процессов восстановления к процессу Пуассона J. Sapagovas, Apie Markovo atstatymo procesų sumų konvergavimą į Puasono procesą